Usefulness of Robinia pseudoacacia in the Treatment of Gastroesophageal Reflux Disease - Agarwal, Radhika (Homœopathic Links, 2019)
Background and Objective Gastroesophageal reflux disease (GERD) is a common condition observed in daily clinical practice. This study was undertaken to explore the usefulness of Robinia pseudoacacia in the treatment of GERD. Traditionally, since many centuries, Robinia pseudoacacia has been in use for various gastric disturbances in physiological doses. This study is an effort to understand its utility in GERD when prescribed on homoeopathic indications.Methods A prospective, observational study was conducted at Bakson Homeopathic College and Hospital, Greater Noida, Uttar Pradesh from 2016 to 2018. Patients who were 20 to 60 years of age suffering from heartburn and regurgitation were screened. Purposive sampling technique was used to enrol 30 patients (17 males and 13 females), who fulfilled the inclusion and exclusion criteria were enrolled in the study. The diagnosis was made on the basis of GERD questionnaire (GerdQ). Robinia pseudoacacia was prescribed in 6C potency in repeated doses to the enrolled patients on the clinical basis of symptom totality. The improvement in patients was assessed using GerdQ which was evaluated at baseline and after the 6 months treatment by using the paired ‘t’ test.Results All enrolled cases completed the follow-up of 6 months. Out of the 30 cases, 1 case was cured, 26 showed a good improvement and 3 did not respond to the treatment. Overall, statistically significant difference was found in pre- and post-treatment GERDQ scores (p < 0.001).Limitations include lack of control arm and prescription on common symptoms due to lack of characteristic symptoms.Conclusion This study has shown positive results in terms of usefulness of Robinia pseudoacacia in the treatment of GERD. Further randomised controlled trial with long-term follow-ups need to be conducted for definite conclusions.
Keywords: gastroesophageal reflux disease; Robinia; homoeopathic; GerdQ